THE DIVERSITY OF HAULS OF TRAWL FISHERMEN ON FISH DISEMBARKATION IN MUARA KAKAP DISTRICT OF KUBU RAYA WEST KALIMANTAN - Joko Apriyadi; Ahmad Mulyadi; Sri Rahayu (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT It has been widely known that the Indonesian enormous fish diversity has reached over 300 species of both breams and sea breams (DKP, 2007). The diversity itself, based on LIPI (2010) has contained about 4000-6000 species all over the territorial waters. There are over 2917 species of breams identified in South East Asia (Kottelat et al 1993). This study is aimed at investigating the diversity of species of hauls of the trawl fishermen on fish disembarkation in Muara Kakap. The method of the study is purposive random sampling with random interviewee. The data was collected as primary and secondary data. The primary data was the fishermen hauls including the number and type. The secondary data was the number of regular hauls, annual hauls, decreasing hauls, the caught-hauls data from Marine and Fisheries Office of West Kalimantan Province as well as the data of rainfall and tide from BMKG. This study was conducted on March until May 2019. Based on the research findings, obtained 26 species of 21 families. 5 species of daily hauls are gelame ketupat (Nibea soldado), ikan selangat (Anodotosma chacunda), ikan gelame bungketo (Pennahia anea), ikan belanak (Mugil dussumieri). The biggest of family Scianidae were found 3 species while Lutjanidae 2 species. The diversity index during the study (H’) was 2,47 classified as average while domination index (C) was 0,12 which means none of the species are dominating. Keywords: Species Composition, District, Scianidae, Lutjanidae